Trend 2000 - 2008. Statistics Canada. CANSIM: Manufacturing - Nonmetallic Mineral and Metal | Country: Canada | Province: Nunavut | Table: Mineral industries, including metals, non-metallic metals and fuels | Variable: Fuel and electricity | Units: , 2000-2008. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. Dataset-ID: 075-001-153. - Statistics Canada (Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc., 2015)
Statistics Canada (2015). CANSIM: Manufacturing - Nonmetallic Mineral and Metal | Country: Canada | Province: Nunavut | Table: Mineral industries, including metals, non-metallic metals and fuels | Variable: Fuel and electricity | Units: , 2000-2008. Data-Planet™ Statistical Ready Reference by Conquest Systems, Inc. [Data-file]. Dataset-ID: 075-001-153. Dataset: Provides statistics on Canadian manufacturers primarily engaged in making nonmetallic mineral products, smelting, and refining ferrous and nonferrous metals from ore, pig, or scrap in blast or electric furnaces. Also coverered are forging, stamping, forming, turning and joining processes to produce ferrous and nonferrous metal products, such as cutlery and hand tools, architectural and structural metal products, boilers, tanks, shipping containers, hardware, spring and wire products, and turned products, as well as bolts, nuts and screws. CANSIM is Statistics Canada's key socioeconomic database. The datasets included here provide statistics on the Canadian population, and the nation’s resources, economy, society, and culture. In addition to conducting a Census every five years, approximately 350 active surveys are conducted on virtually all aspects of Canadian life. Statistics are provided for the nation as a whole, provinces, and other subnational geographies where available. Category: Industry, Business, and Commerce Source: Statistics Canada Established as Canada's central statistical office by the Statistics Act of 1985, Statistics Canada is required to "collect, compile, analyse, abstract and publish statistical information relating to the commercial, industrial, financial, social, economic and general activities and conditions of the people of Canada." Its main objectives are to provide statistical information and analysis about Canada’s economic and social structure and to promote sound statistical standards and practices. http://www.statcan.gc.ca/ Subject: Mineral and Mining Industry, Mineral Production, Manufactured Goods, Manufacturing Businesses, Manufacturing Industry, Mineral Products